2014
DOI: 10.1089/ars.2013.5731
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Biochemistry Methods for Investigating Protein Tyrosine Phosphatases

Abstract: Significance: The protein tyrosine phosphatases (PTPs) are a family of proteins that play critical roles in cellular signaling and influence many aspects of human health and disease. Although a wealth of information has been collected about PTPs since their discovery, many questions regarding their regulation and function still remain. Critical Issues: Of particular importance are the elucidation of the biological substrates of individual PTPs and understanding of the chemical and biological basis for temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 145 publications
(154 reference statements)
0
10
0
Order By: Relevance
“…PTPRC was another upregulated hub gene, encoding a member of the PTP family ( 53 ). PTPs are known to be signaling molecules that regulate a variety of cellular processes, including cell growth, differentiation, mitosis and oncogenic transformation ( 54 ). Clark et al ( 55 ) reported that galectin-3 served an anti-apoptotic role in diffuse large B-cell lymphoma via binding to PTPRC product.…”
Section: Discussionmentioning
confidence: 99%
“…PTPRC was another upregulated hub gene, encoding a member of the PTP family ( 53 ). PTPs are known to be signaling molecules that regulate a variety of cellular processes, including cell growth, differentiation, mitosis and oncogenic transformation ( 54 ). Clark et al ( 55 ) reported that galectin-3 served an anti-apoptotic role in diffuse large B-cell lymphoma via binding to PTPRC product.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations suggest that phosphatase activity is equally important as kinase activity with respect to the regulation of signaling pathways (Myers et al 2001;Bourdeau et al 2005;Dadke et al 2007;Park et al 2009b;Stanford et al 2014). We focused on PTP1B, since it has been reported that the substrates of this phosphatase are Jak2 and Tyk2 but not Jak1 (Myers et al 2001).…”
Section: Ptp1b Modulates Stat Protein Activationmentioning
confidence: 99%
“…44 Na 3 VO 4 is generally thought to bind as a transition state analog to the phosphoryl transfer enzymes, so it has been considered as a common competitive inhibitor for PTP1B. 45 As illustrated in Fig. 4(g), with the increasing Na 3 VO 4 concentrations from 0.03 to 1.7 μM, the color of the dispersion gradually changes from wine red to violet (inset (g), from vial 1 to vial 10), corresponding to the decrease of absorbance at 522 nm and the increase of absorbance at 650 nm.…”
Section: Evaluation For Inhibitor Assaymentioning
confidence: 99%